Physical Separation Bahan Aktif Katoda dari Campuran Hasil CrushingBaterai Lithium-Ion Bekas - Fadillah, Farika Asna; Perdana, Indra; Purnomo, Chandra Wahyu (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The increasing use of electric vehicles in the coming decades makes the recycling of spent li-ion batteries an important topic to develop. Recycling spent li-ion batteries is necessary to extract valuable materials from the battery cathode. Elutriation is one of the separation method to separate the cathode and anode from the blackmass resulting from crushing by utilizing differences in density and terminal velocity. The Elutriation method is attractive to develop because the separation is done by adjusting the fluid velocity and does not use chemicals. In this study, 4 variations of fluid load will be used, namely 24, 27, 30, and 34 mL/min. The blackmass to be elutriated has a size variation between -38 to +53 micrometers. From the results under the elutriator, the cathode mass obtained for fluid load variations of 24, 27, 30, and 34 mL/min are 0.8366, 0.4333, 0.3907, and 0.1349 grams. The highest cathode recovery at a load of 24 mL/min is 97.21% and the cathode fraction is 0.4091. Furthermore, it can increase the cathode composition in the mixture by 48.98% and reduce the anode composition by 18.54%.